The girls with no names [compact disc, unabridged] - Burdick, Serena (Harper Audio, 2020)
Not far from Luella and Effie Tildon's large family mansion in Inwood looms the House of Mercy, a workhouse for wayward girls. The sisters grow up under its shadow with the understanding that even as wealthy young women, their freedoms come with limits. But when the sisters accidentally discover a shocking secret about their father, Luella, the older brazen sister, becomes emboldened to do as she pleases. But her rebellion comes with consequences, and one morning Luella is mysteriously gone. Effie suspects her father has made good on his threat to send Luella to the House of Mercy and hatches a plan to get herself committed to save her sister. But she made a miscalculation, and with no one to believe her story, Effie's escape from the House of Mercy seems impossible-unless she can trust an enigmatic girl named Mable. As their fates entwine, Mable and Effie must rely on each other and their tenuous friendship to survive.